Diabetic ketoacidosis in end stage renal failure patient on maintenance dialysis – key challenges in management - Lim, Xue Meng; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Diabetic ketoacidosis (DKA) is a medical emergency which requires prompt management to prevent mortality. Treatment is complicated in end stage renal failure (ESRF) patients due to their altered physiology in sugar metabolism and fluid haemodynamics. To date, there are only a few case reports illustrating the presentation and management of DKA in ESRF patients and a definite guideline on treatment of DKA in ESRF is seriously lacking. We report here a case of an ESRF patient on maintenance haemodialysis, who develops DKA due to missed insulin, and outline our successful treatment plan. We hope our reported case report research can further contribute to the knowledge of DKA management in ESRF.